2019
DOI: 10.1021/acs.est.8b06773
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interfacial Joule Heating Effect in the Electrochemical Advanced Oxidation Process

Abstract: The electrochemical advanced oxidation process (EAOP) has gained popularity in the field of water purification. During the EAOP, it is in the boundary layer of the anode–solution interface that organic pollutants are oxidized by hydroxyl radicals (•OH) produced from water oxidation. Applying current to an anode dissipates heat to the surroundings according to Joule’s law, leading to an interfacial temperature that is much higher than that of the bulk solution, which is known as the “interfacial Joule heating” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…The positive correlation between the increase in the oxidation rate and the activation energy was in good agreement with the results reported in our previous study. 33 This means that • OH-mediated oxidation of organic compounds occurred at an interfacial temperature that was virtually much higher than the bulk solution, as though the low temperature of the bulk solution did not act on interfacial reactions at all. This is due to the fact that the half-life of • OH is extremely short compared with the rate at which they are produced on the anode surface, making them exist only in a thin layer (i.e., Nernst diffusion layer with a thickness smaller than 1.0 μm 48 ) near the anode surface, and the heating of this layer precedes that of the bulk solution.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The positive correlation between the increase in the oxidation rate and the activation energy was in good agreement with the results reported in our previous study. 33 This means that • OH-mediated oxidation of organic compounds occurred at an interfacial temperature that was virtually much higher than the bulk solution, as though the low temperature of the bulk solution did not act on interfacial reactions at all. This is due to the fact that the half-life of • OH is extremely short compared with the rate at which they are produced on the anode surface, making them exist only in a thin layer (i.e., Nernst diffusion layer with a thickness smaller than 1.0 μm 48 ) near the anode surface, and the heating of this layer precedes that of the bulk solution.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The ohmic heating phenomenon has been universally observed in fuel cells, sterilization, and electrochemical organic synthesis. In our previous studies, we proposed the interfacial Joule heating (IJH) effect to demonstrate the formation of the temperature gradient between the anode/solution interface and the bulk solution in the electrochemical advanced oxidation process. As a result of the IJH effect, the reacted interfacial temperature could reach 70.2 °C, a value mostly doubling that of the bulk solution (33.6 °C) . In this case, organic pollutants are oxidized within the boundary layer of the anode/solution interface (i.e., Nernst diffusion layer with a thickness of several hundred nanometers) at a temperature much higher than that of the bulk electrolyte.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is necessary to transfer heat from the reactor to the outside to keep the temperature at the desired set point. Pei 42 indicated that at 70.2 °C, the concentration of the ˙OH radical used for removing organic pollutants was much lower than the concentration at 25 °C. Panizza 43 pointed out that the current efficiency of the reactor was significantly improved when the temperature in the reactor was reduced from 60 °C to 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is necessary to transfer heat from the reactor to the outside to keep the temperature at the desired set point. Pei 42 indicated that at 70.2 C, the concentration of the cOH radical used for removing organic pollutants was much lower than the concentration at 25 C. Panizza 43 pointed out that the current efficiency of the reactor was signicantly improved when the temperature in the reactor was reduced from 60 C to 20 C. The temperature elds of both reactors were greatly consistent with their velocity elds, in which the temperature eld distribution in the TEAR was more uneven (Fig. 7B), indicating that the spiral mixer can efficiently accelerate heat transfer.…”
Section: Stress and Temperature Enhancement Of The Tearmentioning
confidence: 99%